Switching Analysis in Hybrid OHL-Submarine Cable 500-kV Transmission System - Binhot P. Nababan; Kevin Marojahan Banjar-Nahor; Musa Partahi Marbun; Suwarno; Nanang Hariyanto (IEEE Open Access Journal of Power and Energy)
This study focuses on analyzing switching transients in the upcoming 500 kV Java-Bali Connection (JBC) hybrid OHL and submarine cable project using DIgSILENT PowerFactory software, based on a realistic power system model. Distributed-parameter models with constant parameters of the Bergeron model are utilized. Analysis of the traveling wave effect on the line is conducted, and the integration time step based on the time of the traveling wave is carefully selected. Statistical distributions of energization are produced by varying the circuit configuration and system short-circuit power. It is found that the Switching Withstand Voltage (SWV) during the energization process remain below 1175 kV. The probability distribution is fitted to a normal distribution, with the skewness and kurtosis shown to be skewed to the right and having a lower peak than that of the normal distribution, respectively. When a three-phase short-circuit at the line breaker is induced, the rate of rise of recovery voltage (RRRV) exceeds the IEC standard envelope if only one circuit is operating. In this contribution, switching analysis during no-load energization and de-energization in the planning stage of the mixed OHL-submarine cable is examined.